Teori Netralisasi Dalam Kriminologi: Membenarkan Kekerasan Melalui Solidaritas - Ciek Julyati Hisyam; Arifin Yusli; Elisabeth Kewa Making; Risma Ayu Anjali Pratama; Roby Priambodo; Ryan Fathurrahman Baihaqqi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Violence is an expression carried out by someone as a form of solidarity or a reaction from someone to another person's actions. Violence as justification refers to the use of justifications by criminals to neutralize feelings of guilt for their violent actions. The aim of this research is to explain someone's violent actions as a form of solidarity with a friend using neutralization theory. This research was conducted using a descriptive method with a qualitative approach carried out through data collection techniques by in-depth interviews with informants located in correctional institutions. The results of this research show that violence can occur because of a person's sense of concern for his friend as a form of solidarity.